2007
DOI: 10.1007/s10750-007-8615-2
|View full text |Cite
|
Sign up to set email alerts
|

Sediment diatom assemblages and composition of pore-water dissolved organic matter reflect recent eutrophication history of Lake Peipsi (Estonia/Russia)

Abstract: A paleolimnological approach was used for the assessment of the recent eutrophication history and identification of possible reference conditions in the large, shallow, eutrophic Lake Peipsi. Lake Peipsi is the fourth largest lake by area, and the largest transboundary lake in Europe, being shared between Estonia and Russia. Lake Peipsi has been anthropogenically impacted over a longer time-scale than that covered by instrumental limnological monitoring. The 210 Pb record and down-core distribution of fly-ash … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 26 publications
4
37
0
Order By: Relevance
“…According to paleolimnological evidences, the eutrophication of L. Peipsi was escalated in 1970-1980s (Heinsalu et al, 2007). The eutrophication history is similar also for L. Võ rtsjä rv (Nõ ges & Jä rvalt, 2004).…”
Section: Discussionmentioning
confidence: 90%
“…According to paleolimnological evidences, the eutrophication of L. Peipsi was escalated in 1970-1980s (Heinsalu et al, 2007). The eutrophication history is similar also for L. Võ rtsjä rv (Nõ ges & Jä rvalt, 2004).…”
Section: Discussionmentioning
confidence: 90%
“…The PCA PC2 suggested that NaOH-LMW-NRP derived primarily from OM (Table 3). Detailed investigation of sediment pore-water fluorescence properties in L. Peipsi showed that aquatic production in the lake increased during the second half of the twentieth century, resulting in a greater autochthonous OM supply to the sediments and a change in accumulated humic substances (Heinsalu et al 2007). Therefore, the whole NaOH-NRP can be influenced by humic substances in the sediments.…”
Section: Mobile Phosphorusmentioning
confidence: 99%
“…For the 210 Pb chronology, the CRS model (Constant Rate of Supply; Appleby et al, 1986) was applied. The methodology, results and reliability of the chronology are presented and discussed in detail in Heinsalu et al (2007).…”
Section: Sediment Coring and Datingmentioning
confidence: 99%
“…(Lower panel) Age-related changes in the characteristics of pore-water dissolved organic matter (k-p). For comparison, the profiles of major sediment constituents (q, r) and lithology (s) (reprinted with permission from Heinsalu et al, 2007) are also shown. Abbreviations: Chl-Chlorophyll; Echi-Echinenone; ZeaZeaxanthin; Cantha-Canthaxanthin; pDOC-Pore-water dissolved organic carbon; M w and M n -Weight-average and number-average molecular weight, respectively; AI-Aromaticity index calculated as the ratio between absorbances at 250 and 365 nm (A 250 /A 365 ); LMW-Low molecular weight; MMW-Medium molecular weight; HMW-High molecular weight; OM-Organic matter; dw and ww-Dry and wet weight of sediments, respectively.…”
Section: Pigment Stratigraphymentioning
confidence: 99%
See 1 more Smart Citation